“For example”: On the rhetorical, epistemological and practical sense of examples (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
Common examples and exemplary similitudes have been an ancient andquotidian means for acquiring competence in life and discourse performance. But, for philosophical discourse, examples become a problem: our philosophical traditions undervalue examples (in the name of conceptual logic and demonstrative reasoning), and, at the same time, tend to consecrate some kind of paradigm as an exemplary model. In this article we pay attention to the efficacy of constructing intermediate cases. So, we explore semiotic, pragmatic and rhetorical aspects related to the act ofsetting an example, and we compare examples with another enouncement means like literal quotations, illustrations and metaphors. We also take seriously a certain “paradigmatic turn” in contemporary epistemology, which emphasizes the role of models and shared examples, in scientific investigation. Finally, we discuss the practical difficulties of setting exemplary models in times of exception: when the “unjustifiable” becomes a norm, we can only give our testimony.
Keywords: Example; illustration; model; paradigm; testimony